Upaya Guru PAI Dalam Menanamkan Nilai-Nilai Pendidikan Karakter Islami Pada Peserta Didik - Rahmah, Rahmah; Maharani, Dewi (An-Nuha, 2024)
Based on the research found, there is a uniqueness in changing the name of the school, which was previously called SMK Citra Bangsa to SMK Al-Aqsyar Islamic School Bogor in 2021 based on the wishes of the Am Badar Foundation, which aims to instill the shari'ah creed, which stands for "Al-AqSyar". Researchers know that there are school concerns about students who have not thought critically about the times from technology, speaking and dressing styles that are not by Islamic guidance. The purpose of this study is to find out the teachers' efforts in instilling Islamic character education values at SMK Al-Aqsyar Islamic School Bogor. This research uses qualitative research methods, through a qualitative descriptive approach. Data collection techniques were carried out through observation, interviews with the principal, two PAI teachers, the head of student affairs and six students at SMK Al-Aqsyar Islamic School Bogor and documentation. The results showed the efforts of PAI teachers in instilling Islamic character values in students by implementing 5S habituation (Salam, Sapa, Sopan, Santun and Smile) and morning dhikr and Dhuha prayer activities. Islamic character values found in students are Iman, Islam and Ihsan.